1999
DOI: 10.1118/1.598813
|View full text |Cite
|
Sign up to set email alerts
|

Dose model for a beta-emitting stent in a realistic artery consisting of soft tissue and plaque

Abstract: A model for the description of the near-field dose deposition from a 32p impregnated stent in an arterial system consisting of soft tissue and dense plaque is presented. The model is based on the scaling property of the dose-point-kernel (DPK) function which is extended to a heterogeneous medium consisting of a series of layers of different materials. It is shown that, for each point source originating from the stent surface, the DPK function for water can be scaled consistently along the path through the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…The first medical products to show significant results in a clinical trial for the reduction in in-stent restenosis following balloon angioplasty were intravascular brachytherapy sources, although they were eventually superseded to a great extent by drug-eluting stents. During the development stages of IVBT, the radiation sources used in the coronary vessel clinical trials included seed trains ͑with 16,17 and without [18][19][20][21][22] interseed spacing͒, wires, 23-37 radioactive stents, [38][39][40] radioactive liquid filled balloons, 41-43 radioactive gas filled balloons, 44 and balloons impregnated with radioactivity. 45,46 In addition there were peripheral vascular trials 47 using a HDR…”
Section: Viia1 Backgroundmentioning
confidence: 99%
“…The first medical products to show significant results in a clinical trial for the reduction in in-stent restenosis following balloon angioplasty were intravascular brachytherapy sources, although they were eventually superseded to a great extent by drug-eluting stents. During the development stages of IVBT, the radiation sources used in the coronary vessel clinical trials included seed trains ͑with 16,17 and without [18][19][20][21][22] interseed spacing͒, wires, 23-37 radioactive stents, [38][39][40] radioactive liquid filled balloons, 41-43 radioactive gas filled balloons, 44 and balloons impregnated with radioactivity. 45,46 In addition there were peripheral vascular trials 47 using a HDR…”
Section: Viia1 Backgroundmentioning
confidence: 99%
“…Nevertheless, stents have not been entirely successful in eliminating restenosis due to tissue proliferation, and have actually been found to stimulate neointimal hyperplasia in 20-30% of the cases within six to twelve months following angioplasty (Fox, 2002). In-stent restenosis remains problematic, particularly in smaller vessels and longer lesions (Janicki et al, 1999) with rates ranging anywhere from 31-50% as reported by several animal and clinical studies (Fischell et al, 2000).…”
Section: Angioplasty and Stentingmentioning
confidence: 99%
“…The dose distribution generated by the beta particles emitted from the radioisotope was computed at distances ranging from 0.1 to 3 mm from the stent surface. A later study by Janicki et al (1999) introduced a new model taking into account the scaling property of the dose point kernel function which can be extended to a heterogeneous medium with a density different to that of water. Because in a realistic artery the presence of plaque can allow attenuation of the beta particles, incorporating plaque density in a theoretical model has some advantageous effects.…”
Section: Dosimetry Of Radioactive Stentsmentioning
confidence: 99%
See 2 more Smart Citations